An interpersonal pragmatic perspective on seductive discourse - Jim O’DRISCOLL (E-REA)
This paper explores the interpersonal pragmatic aspect of seductive discourse (SD). It demonstrates that SD – understood as getting people to do, believe or feel what you want them to do, believe or feel – is more than a matter of propositional content and also more than a matter of the linguistic finery in which this content is dressed. This is because all language forms and all speech acts depend for their effects on context.Furthermore, it demonstrates that SD in the sense above is an inherent part of everyday interaction and at the centre of relationships. The fact that these desires often take the form of background, half-conscious or unconscious expectations should not blind us to the fact that this concern for self-presentation is ever-present. This is one reason why, although SD is often necessarily covert, it is not thereby inherently deceptive. The other reason is that we simply do not have the time to present ourselves fully and explicitly. The exigencies of interaction force us all to act on impressions.Among other pragmatic concepts, a major tool for the exploration of these inevitable interactional realities is the concept of face. Following a brief account of these concepts, and the interpersonal pragmatic perspective more generally, the demonstration of the above claims is achieved through the analysis of three very different cases: an excerpt from a TV comedy, a (generic) academic conference presentation and a (particular) incident during a rugby match.